Morphological variation in a conservative structure: the scapulocoracoids in Sympterygia acuta Garman, 1837 and Sympterygia bonapartii Müller & Henle, 1841 (Chondrichthyes: Rajidae) - Jurado, Carlos D.; Mabragaña, Ezequiel; Astarloa, Juan Martín Díaz De (Zootaxa, 2017)
Scapulocoracoid variation in Sympterygia acuta and S. bonapartii was analyzed inter- and intraspecifically, and the utility of this structure as a diagnostic character in skates was evaluated. Skeletal pieces were obtained from a total of 85 specimens collected in coastal waters of northern Argentina in 2011 and 2012. Morphometric variation was analyzed using non parametric tests. Morphologic variation was qualitatively and quantitatively evaluated by comparing number, shape and arrangement of posterior fenestrae. Scapulocoracoids of both species are rectangular in shape and expanded anteroposteriorly, but those of S. bonapartii were more expanded. Differences in shape, both in males and females, were reflected in the ANOSIM test. Greatest Height and Height of Rear Corner were the variables that most contributed to the differences found between both species. These differences in morphology agree with previous descriptions. No sexual dimorphism was observed regarding scapulocoracoids in S. acuta, and only a slight variation between males and females of S. bonapartii was found. Number of postdorsal and postventral fenestrae was highly variable. At least five scapulocoracoid morphotypes for S. acuta (with two to six fenestrae) and seven scapulocoracoid morphotypes for S. bonapartii (with three up to nine fenestrae) were identified. However, patterns of fenestrae arrangement were also very diverse in both species. Therefore, a broad variation in fenestrae number and pattern, especially postdorsal ones, was shown in both species. These results indicate that caution needs to be taken when using the scapulocoracoids not only in phylogenetic studies but also in descriptions of new species.